Reproductive fitness of Diadegma semiclausum Hellen (Hymenoptera Ichneumonidae) in response to host density - Khatri, D.; He, X.Z.; Wang, Q. (New Zealand Plant Protection, 2012)
Diadegma semiclausum is an important larval parasitoid of diamondback moth (DBM) Plutella xylostella The present study investigated the reproductive fitness of D semiclausum females in response to host densities of 5 and 30 DBM larvae per cabbage seedling per day Both the number of hosts parasitised and the number of female progeny produced over the life of the parasitoid were significantly greater in the 30 than the 5 host density (hosts parasitised 60131 versus 12015 and female progeny produced 6710 versus 122) (P